Friel and his "sisters" - Nicholas Grene (Ilha do Desterro)
This essay, occasioned by a revival of Brian Friel's version of Chekhov's Three Sisters at the Abbey Theatre in 2008, considers the circumstances surrounding its first production by the Field Day Theatre Company in 1981, and the motivation behind the decision to translate Chekhov's text into a specifically Irish dialect of English. It also analyses how Friel's plays since that date, notably the award-winning Dancing at Lughnasa (1990), have changed our perspective on the play.